Analisis Perlindungan Konsumen dalam Keamanan Transaksi di Aplikasi Belanja Online Studi pada Pengguna Shopee - Falentina Putri Winata; Romi Faslah (Jurnal Ekonomi dan Bisnis Digital, 2025)
Along with the development of digital technology, it has had an impact on the increasingly significant growth of e-commerce. E-commerce is the main alternative in buying and selling transactions without having to meet directly or have physical contact with sellers and buyers. With e-commerce, consumers are given the convenience of shopping with wide access and reach, besides that the payment process offered has many choices, making it easier for consumers to transact. However, this convenience also presents new challenges in terms of consumer protection. This research aims to find out how consumer data protection in transactions that occur on online shopping platforms, where this research focuses on the Shopee application. The research method used is a qualitative method related to collecting data on the Shopee e-commerce platform, reading and taking notes from consumer experiences in transactions. The results show that although there are regulations that protect consumers, their implementation is still not optimal due to the lack of consumer awareness of their rights, weak supervision, and low access to dispute resolution mechanisms. Therefore, it is necessary to increase consumer education, strengthen the role of the government, and optimize e-commerce platforms in ensuring the protection of consumer rights. This research is expected to contribute to the improvement of the consumer protection system in the digital era